If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9-6(w+5)=0
We simplify the equation to the form, which is simple to understand
-9-6(w+5)=0
Reorder the terms in parentheses
-9+(-6w-30)=0
Remove unnecessary parentheses
-9-6w-30=0
We move all terms containing w to the left and all other terms to the right.
-6w=0+9+30
We simplify left and right side of the equation.
-6w=+39
We divide both sides of the equation by -6 to get w.
w=-6.5
| 3(8x-4)-1(2x-10)=4 | | 7(x+3)=-4(5-4x)-9x | | -10a^3b^2+12ab=0 | | X^2+7x-12x-84=-70 | | F(3)=-4x+1 | | 4e^5x=5e^6x | | -7-(-3-2q)-10=0 | | jx+my=x | | 7x^2+13x=2x^2-20x+14 | | 5a+15=35+23 | | 4(2v+3)-14v= | | 216=(2x+14)(x+4) | | 2s-3=60 | | 3x-3=4x-17 | | Ax+cx=b+d | | 3x+8-x=8+3x-6 | | 2y+2y-19y+35=0 | | 50.09+3.75x=800 | | 9x^2+12x=-9 | | 2.1+x=5.4 | | -3(4y-7)+2(3y+8)= | | (6x-4)+(4x+39)=180 | | 3x+4=17x+6 | | b-31b= | | x^2=(2x-7)(2x+13) | | -[5x-(3x+1)]=-6-[3(2x-4)-2x] | | (M-3)SQUARED(M-4)=0 | | 5Y^2-Y-12=0 | | 12(x+4)=14(x-2) | | 67+4x+15=90 | | X^2-Y^2-6X-4Y+4=0 | | -6a^6+4a^5-2a^4= |